FIRE: Fast Incremental Recommendation with Graph Signal Processing - Xia, Jiafeng; Li, Dongsheng; Gu, Hansu; Liu, Jiahao; Lu, Tun; Gu, Ning (TheWebConf 2022, 2022)
Real-world recommender systems are incremental in nature, in which new users, items and user-item interactions are observed continuously over time. Recent progresses in incremental recommendation rely on capturing the temporal dynamics of users/items from temporal interaction graphs, so that their user/item embeddings can evolve together with the graph structures. However, these methods are faced with two key challenges: 1) model training and/or updating are time-consuming and 2) new users and items cannot be effectively handled. To this end, we propose the fast incremental recommendation (FIRE) method from a graph signal processing perspective. FIRE is non-parametric which does not suffer from the time-consuming back-propagations as in previous learning-based methods, significantly improving the efficiency of model updating. In addition, we encode user/item temporal information and side information by designing new graph filters in the proposed method, which can capture the temporal dynamics of users/items and address the cold-start issue for new users/items, respectively. Experimental studies on four popular datasets demonstrate that FIRE can improve the recommendation accuracy...